2019
DOI: 10.1136/vr.105378
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and risk factors for acute laminitis in horses treated with corticosteroids

Abstract: A retrospective treated versus untreated study (study 1) and multicentre prospective cohort study (study 2) were undertaken to determine the prevalence of, and risk factors associated with, acute laminitis in horses treated with corticosteroids. All old treated with corticosteroids January–December 2014 (study 1) and January 2015–February 2017 (study 2) by two first opinion and referral hospitals in UK were included. Additionally, an untreated animal was identified for each treated animal (study one). Signalme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 31 publications
3
31
0
Order By: Relevance
“…Causative mechanisms have been proposed and evidence for these has been reviewed 1‐3 . However, a recent knowledge summary 4 found “no conclusive evidence to support a causal association between therapeutic systemic corticosteroid administration and the development of laminitis in healthy adult horses/ponies” and two recent studies found no association between corticosteroid use and laminitis 5,6 …”
Section: Introductionmentioning
confidence: 99%
“…Causative mechanisms have been proposed and evidence for these has been reviewed 1‐3 . However, a recent knowledge summary 4 found “no conclusive evidence to support a causal association between therapeutic systemic corticosteroid administration and the development of laminitis in healthy adult horses/ponies” and two recent studies found no association between corticosteroid use and laminitis 5,6 …”
Section: Introductionmentioning
confidence: 99%
“…In the retrospective study, 1 per cent of horses in both the glucocorticoid and control groups developed laminitis. In the cohort study, 10 of 1565 glucocorticoid‐treated horses developed laminitis, giving a period prevalence of laminitis of only 0.6 per cent – much lower than published estimates of the laminitis prevalence in the general equine population 3 . The authors identified links between laminitis and being a pony, being overweight, having a history of laminitis and having an endocrinopathy.…”
mentioning
confidence: 94%
“…In a paper summarised on p 82 of this issue of Vet Record, Potter and colleagues provide further evidence to help us determine whether there is indeed any link between glucocorticoid administration and laminitis. 3 They performed both a retrospective case-control study of 205 horses and a prospective cohort study of 1565 horses treated with glucocorticoids. These are not perhaps the 'big data' studies that would be desirable to provide a more robust answer to the question of whether glucocorticoids can cause laminitis, but they are another piece of a jigsaw puzzle that appears to be revealing a clear picture.…”
mentioning
confidence: 99%
See 2 more Smart Citations